Analisis Peningkatan Keandalan Jaringan CATV Pada PT. Chevron Pacific Indonesia Dari Sistem Coaxial Cable ke Sistem Fiber Optic - Wijaya, Indra Putra; Sari, Linna Oktaviana; Safrianti, Ery (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Chevron Pacific Indonesia ( CPI ) is one company that has a long establish the CATV network operation using coaxial cable system. CATV over time networks with this system experienced a slump of quality or reliability. This is certainly not desired by the CPI, due to the failure resulting in service less than the maximum. Therefore CPI change the system using fiber optic system that can boost reliability. Reliability is one of the important performance, because the results of the reliability prediction can be used to determine the option to use an instrumentation and implementation on a CATV network. Reliability parameters of a network include the availability (availability), system downtime and Mean Time to Failure (MTTF) or prediction of the lifetime of a network. By analyzing the above parameters obtained the level of system CATV network availability in the CPI, rumbai district greater than 99.99%. The level of availability (availability) is obtained in fiber optic systems have an average 99.9923655%, with the value system down time at 40.1266692 min / year, and Mean Time to Failure (MTTF) is 29.0259193 years. With the above calculation can be concluded that the fiber optic system on CATV networks in the CPI has reached the applicable standards, even much better.Keywords: Down Time System, CATV networks, coaxial cable, fiber optic reliability Engineering Markov Methode